INKONSISTENSI RASM AL-QUR’AN DALAM MANUSKRIP NUSANTARA: ANTARA KAIDAH UTSMĀNĪ DAN TRADISI IMLĀ’Ī - Rafly, Muhammad (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study examines the dynamics of Qur'ānic writing in ancient manuscripts of the archipelago to understand the interaction between the standard Uthmānī rasm and local traditions. This study is conducted with a descriptive-analytical approach through the analysis of manuscripts from Madura, Gunungkidul, Padang Panjang, and Priangan, as well as a review of classical tafsir literature by al-Qurṭubī and al-Qusyairī as a basis for interpretation. The results show that mushaf copying in the archipelago is adaptive, with mixed use of the Uthmānī and Imlā'ī rasm, as well as deviations in harakat and punctuation influenced by technical limitations and the tradition of oral education. The socio-cultural function of the mushaf is very prominent, as seen from its role as a family heirloom, a symbol of religious identity, and a means of community spirituality. Variations in rasm forms such as tā' marbūṭah and tā' maftūḥah also have important implications for the interpretation of verses, especially in an esoteric perspective. These findings show that the ancient mushaf of the archipelago is not only a religious text, but also a scientific and cultural heritage that reflects the richness of local Islamic expressions, so it is worth preserving as part of the community's religious identity.